Given f (x) = x+2, g (x) = x+3 Find the following a.(f+g)(x) b.(f—g)(x) c.(fg)(x)
![Given F X X2 G X X3 Find The Following Afgx Bfgx Cfgx class=](https://ph-static.z-dn.net/files/d80/4f682b7f1b31b0712ed4e96955776187.jpg)
a. (f+g)(x) = (x+2 + x+3)(x) = (x•2+6)(x) = (2x+5)(x) = 3x+5
b. (f-g)(x) = (x+2 - x+3)(x) = (2-3)(x) = (-1)(x) = -1x
c. (fg)(x) = (x+2 • x+3)(x) = (x² + 6)(x) = (x²+5)(x) = x³+5
d. (f/g)(x) = (x+2 / x+3)(x) = (2x/5)(x) = 3x/5
e. (f•g)(x) = (x+2 • x+3)(x) = (x² + 5)(x) = (x²+5)(x) = x³+5
f. (g•f)(x) = (x+3 • x+2)(x) = (x² + 5)(x) = (x²+5)(x) = x³+5